Internal carotid, external carotid and vertebral artery blood flow responses to 3 days of head‐out dry immersion. Issue 10 (24th August 2017) - Ogoh, Shigehiko; Hirasawa, Ai; de Abreu, Steven; Denise, Pierre; Normand, Hervé
Abstract : New Findings: What is the central question of this study? The extent to which weightlessness associated with a fluid shift from the peripheral to the central circulation influences the blood flow in each cerebral artery remains unknown. The present study was designed to explore the effect of short‐term weightlessness conditions on both anterior and posterior cerebral blood flow. What is the main finding and its importance? Short‐term weightlessness affects both anterior and posterior cerebral vasculature. However, a heterogeneous cerebral blood flow response in each cerebral artery did not occur during 3 days of dry immersion. We have recently demonstrated that a heterogeneous cerebral blood flow (CBF) response in each cerebral artery might contribute to the maintenance of circulatory homeostasis in the brain. However, the extent to which weightlessness associated with a fluid shift from the peripheral to the central circulation influences the distribution of CBF in each cerebral artery remains unknown. We hypothesized that a dry immersion‐induced fluid shift (weightlessness conditions) would cause a heterogeneous CBF response in each cerebral artery. During and after 3 days of dry immersion, the blood flows in the internal carotid (ICA), external carotid (ECA) and vertebral arteries (VA) were measured by Doppler ultrasonography using an 8 MHz linear transducer. Although the 3 days of dry immersion and the 2 days recovery period did not change the blood flow in each cerebral artery, the conductance in both ICA and VA decreased during dry immersion on days 2 and 3 (ICA, 2.95 and 3.23 ml min −1  mmHg −1 ; VA, 1.10 and 1.05 ml min −1  mmHg −1, respectively) from the baseline (ICA, 3.47 ml min −1  mmHg −1, P  = 0.027; VA, 1.23 ml min −1  mmHg −1, P  = 0.004). In addition, Pearson correlation analysis demonstrated that the 3 days of dry immersion induced a decrease in cardiac output ( P  = 0.004) that was associated with changes in ICA ( P  = 0.046) and VA blood flow ( P  = 0.021), but not ECA blood flow ( P  = 0.466). These findings suggest that short exposures to weightlessness, acting via a cephalad redistribution of fluid volume and blood flow in the human body, influenced the cerebral vasculature in each cerebral artery but did not cause a heterogeneous CBF response in each cerebral artery. Abstract :